Hak Milik dan Pengelolaan Harta Benda dalam Perspektif Hukum Konstitusi Indonesia - Risman Setiawan (Jurnal Ilmu Sosial dan Humaniora, 2025)
Property rights and property management are essential human rights guaranteed by the Indonesian Constitution. In the Indonesian context, property rights are regulated in Article 28H paragraph (4) of the 1945 Constitution and Law Number 5 of 1960 concerning Agrarian Principles, which emphasizes that ownership must have a social function. This study examines the theory and implementation of property rights by examining the balance between individual and public interests. The analysis shows that although property rights protection has been regulated normatively, in practice there is still inequality in access to resources and weak law enforcement. Strengthening policies that guarantee justice and sustainability in property management in Indonesia is needed.